2016
DOI: 10.1111/odi.12454
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nervous system involvement in primary burning mouth syndrome—results of a pilot study

Abstract: Our results in neurophysiologically optimally characterized BMS patients confirm that pure focal small fiber neuropathy of the oral mucosa has a role in the pathophysiology of primary BMS. Furthermore, BMS may be related to a more generalized, yet subclinical peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 35 publications
4
62
0
1
Order By: Relevance
“…Epithelial atrophy has also been described in a study that concluded that it could lead to greater exposure of nervous terminations and the consequent symptoms described for this syndrome 61 .Low density of intraepithelial nervous fibers was observed on area and length basis in samples of the tongue dorsum mucosa 62 .…”
Section: Histological Changes In the Oral Mucosamentioning
confidence: 86%
See 1 more Smart Citation
“…Epithelial atrophy has also been described in a study that concluded that it could lead to greater exposure of nervous terminations and the consequent symptoms described for this syndrome 61 .Low density of intraepithelial nervous fibers was observed on area and length basis in samples of the tongue dorsum mucosa 62 .…”
Section: Histological Changes In the Oral Mucosamentioning
confidence: 86%
“…Interestingly, QST may help understand the neuronal mechanisms involved in various kinds of chronic pain. These tests evaluate the function of a variety of nervous fibers and detect both sensory gains and losses, and are being adapted to investigate the intraoral somatosensory function 32,62,133 . The changes associated with BMS that have thus far been described include the reduction of thermal sensitivity and low scores for tonic painful stimuli in the oral cavity, as well as lower thresholds of pain caused by heat on the tip of the tongue, anomalies in the BR, and qualitative alterations of saliva 5 .…”
mentioning
confidence: 99%
“…Alterations in both the central and peripheral nervous systems of BMS patients are reported using a variety of neuro-exploratory investigations 121, 122 . There are 3 subclasses of neurophysiologic pain described for BMS patients: peripheral small fiber neuropathy, subclinical major trigeminal neuropathy, and central pain possibly related to deficient dopaminergic inhibition 121, 123, 124 .…”
Section: Burning Mouth Syndrome (Bms)mentioning
confidence: 99%
“…Symptoms associated with BMS vary and may have a negative impact on oral health-related quality of life in patients with BMS (1). McMillan et al (2) reported that, so far, no therapy has been proven to be effective or ineffective in patients with BMS. To date, there is no clear evidence that there is dysfunction of central and/or peripheral nervous system in patients with BMS (3,4).…”
Section: Introductionmentioning
confidence: 99%